Critical current and flux dynamics in Ag-doped FeSe superconductor. (23rd December 2016) - Galluzzi, A; Polichetti, M; Buchkov, K; Nazarova, E; Mancusi, D; Pace, S
Abstract: The measurements of DC magnetization as a function of the temperature M(T), magnetic field M(H), and time M(t) have been performed in order to compare the superconducting and pinning properties of an undoped FeSe0.94 sample and a silver doped FeSe0.94  + 6 wt% Ag sample. The M(T) curves indicate an improvement of the superconducting critical temperature and a reduction of the non-superconducting phase Fe7 Se8 due to the silver doping. This is confirmed by the field and temperature dependent critical current density Jc (H, T) extracted from the superconducting hysteresis loops at different temperatures within the Bean critical state model. Moreover, the combined analysis of the Jc (T) and of the pinning force Fp (H/Hirr ) indicate that the pinning mechanisms in both samples can be described in the framework of the collective pinning theory. The U*(T, J) curves show a pinning crossover from an elastic creep regime of intermediate size flux bundles, for low temperatures, to a plastic creep regime at higher temperatures for both the samples. Finally, the vortex hopping attempt time has been evaluated for both samples and the results are comparable with the values reported in the literature for high Tc materials.